Metabolic syndrome and cardiovascular risk among adults - Hunain, Reem; Reddy T, Sravan Kumar; Hande, H Manjunath; KN, Shivashankar; Saravu, Kavitha; Mallya, Sneha Deepak (Indian Journal of Community Health, 2018)
Background: Mortality and morbidity due cardiovascular diseases in India is on the rise. Metabolic Syndrome which is a collection of risk factors of metabolic origin, can greatly contribute to its rising burden. Aims & Objectives: The present study was conducted with the objective of estimating the prevalence of metabolic syndrome and 10-year cardiovascular risk among adults. Material & Methods: This hospital-based study included 260 adults aged 20-60 years. Metabolic Syndrome was defined using National Cholesterol Education Program –Adult Treatment Panel -3 criteria. The 10 year cardiovascular risk was estimated using Framingham risk scoring. Results: The overall prevalence of metabolic syndrome among the study participants was 38.8%. Age (41-60yrs), male gender and daily consumption of high salt items were positively associated with metabolic syndrome whereas consumption of occasional high sugar items showed an inverse association with metabolic syndrome. According to Framingham Risk Scoring, 14.3% of the participants belonged to intermediate/high risk category. Conclusion: With a high prevalence of metabolic syndrome and a considerable proportion of individuals with intermediate to high 10 yr CVD risk, there is a need to design strategies to prevent future cardiovascular events.